Analisis Yuridis Aborsi Korban Perkosaan dalam Perspektif Hukum Pidana dan Undang-Undang Kesehatan - Waruwu, Charidion; Irawati, Arista Candra (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Abortion due to rape is a complex issue in the Indonesian legal system because it involves the right to life of the fetus, women's human rights, and health and criminal aspects. On the one hand, the criminal code criminalizes abortion, while the Health Law provides exceptions in certain cases, including pregnancy due to rape. This difference in legal approach creates uncertainty in the implementation of policies and victims' access to safe and legal health services. This study aims to analyze the legal regulations regarding abortion for rape victims from the perspective of criminal law and health and to compare the implementation of the two regulations in practice. This study uses a normative juridical method with a statutory approach and a case approach. The results of the study show that although the Health Law allows abortion under certain conditions, its implementation still encounters obstacles, especially in the aspect of overlapping regulations, limited access for victims to legal health services, and legal uncertainty for medical personnel who perform abortions. The disharmony between the Criminal Code and the Health Law results in obstacles for victims in obtaining their rights. This finding emphasizes the need for harmonization of regulations between criminal law and health law so that abortion policies in rape cases can be implemented effectively and fairly. In addition, legal protection for victims and medical personnel must be strengthened to ensure that justice and women's health rights are optimally fulfilled.